Occurrence of antibiotic resistant Salmonella spp. in stray and owned cats - Mohsin, Nur Farawahidah (2016)
Salmonellosis is an important zoonotic disease worldwide. The organisms reside commonly in the gastrointestinal tracts. Cats are most widely kept pet animals, yet the risk that these animals pose for transmission of Salmonella to humans is unclear. Free roamer and stray cats are potential candidates for Salmonella carriage and might contribute actively to the contamination of environment. The objectives of this study were to determine the occurrence of Salmonella spp. and to determine the antimicrobial resistance of Salmonella spp. in stray and owned cats. A total of 60 rectal swab samples were collected which consisted of 30 from owned cats at veterinary clinics and individual owners and the other 30 samples were taken from stray cats at residential areas and food stalls. Out of 60 cats, only three (5%) were positive for Salmonella spp. which were from stray cats (10%). The Salmonella spp. isolated were tested against six different antibiotics namely ampicillin, chloramphenicol, ciprofloxacin, gentamicin, sulfamethoxazole-trimethoprim and nalidixic acid. All three (100%) isolates were resistant to ampicillin, but susceptible to ciprofloxacin, and one (33%) isolate was susceptible to gentamicin and chloramphenicol. This could be expected as stray cats are often exposed to intestinal infection with Salmonella species than pet household cats. Stray cats may pose a potential threat to public health and their faecal materials may play significant roles in the contamination of environment.